Tren Topik Pemberitaan Pasca Pemilihan Presiden pada Portal Berita Online - Puspita Ningtias; Nining Sudiar; Hadira Latiar (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2020)
The purpose of this research is to find out, explain, and analyze the trends of the Post Presidential Election news topics on the online news portal Detik.com and Tribunnews.com 2019. This research method uses quantitative descriptive methods. The results of research from 2 online news portals during the post-presidential election, 17 April to 22 May namely the detik.com portal issued the most number of Prabowo-Sandi news as many as 652 news, while the Jokowi-Amin pair 586 news. Tribunnews.com portal issued the most topics on the Jokowi-Amin couple as many as 537, while the Prabowo-Sandi couple had 536 news. Indicators of topic trends are the direction of the portal detik.com Jokowi-Amin news portal with positive news direction 63 or (10.75%), negative news direction 16 or (2.73%), and neutral news direction 507 or (86.52% ). In the Prabowo-Sandi pair who share positive news 67 or (10.28%), then the direction of negative news 47 or (7.21%), while the neutral news direction is 538 or (82.52%). Meanwhile, the online news portal Tribunnews.com released the news of the Jokowi-Amin pair in the direction of positive news 54 or (10.06%), negative news direction 27 or (5.03%), and neutral news direction 537 or (84.92%). Tribunnews.com released the Prabowo-Sandi pair with 57 or (10.6%) positive direction, 45 or (8.40%) negative direction, while the neutral news direction was 434 or (80.97%).